1988
DOI: 10.1016/0735-1097(88)90214-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of left atrial systolic time intervals in hypertensive patients using Doppler echocardiography: Relation to fourth heart sound and left ventricular wall thickness

Abstract: The concept of left atrial systolic time intervals and Doppler echocardiography were used in a quantitative assessment of left atrial function in relation to the presence or absence of a fourth heart sound and to left ventricular hypertrophy in 47 patients with hypertension. Left atrial systolic time interval indexes included atrial pre-ejection period (the time between the onset of an electrocardiographic P wave and the onset of left ventricular inflow during atrial systole [A wave]), corrected atrial pre-eje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The patients were in a partial left lateral decubitus position when they were examined, and special attention was taken to avoid misleading angulation of the left ventricular long axis in relation to the ultrasound beam. 26 All echocardiograms were taken by an experienced examiner and were read independently by two investigators. Left ventricular dimensions and wall thickness were measured using the leading edge technique, according to the recommendation of the American Society of Echocardiography.…”
Section: Measurementsmentioning
confidence: 99%
“…The patients were in a partial left lateral decubitus position when they were examined, and special attention was taken to avoid misleading angulation of the left ventricular long axis in relation to the ultrasound beam. 26 All echocardiograms were taken by an experienced examiner and were read independently by two investigators. Left ventricular dimensions and wall thickness were measured using the leading edge technique, according to the recommendation of the American Society of Echocardiography.…”
Section: Measurementsmentioning
confidence: 99%
“…Figure 3 shows that on average, patients with an S 4 had a leftward-and upward-shifted EDPVR curve, signifying that these patients had stiffer ventricles. Because the β-coefficient, but not the α-coefficient, correlated with the S 4 , it was important to show that the EDV 20 (the calculated EDV at an idealized EDP of 20 mmHg) was smaller in patients with an S 4 compared with those without an S 4 . This finding shows that when the α-and β-coefficients are examined together in the equation EDP = αEDV β , they combine to produce an EDPVR curve that is leftward and upward shifted in the S 4 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we found that several diastolic stiffness parameters, including the EDP/SV and E/E'/SV ratios, and a leftward-and upward-shifted EDVPR curve, were all independently associated with the S 4 . By performing a comprehensive invasive-and non-invasive study of the S 4 , we were able to go beyond prior studies which were limited by studying only mitral inflow characteristics on echocardiography (4,5,18), or which included smaller numbers of patients (2,4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators have applied left atrial wall motion, left atrial volume or systolic time interval by M-mode echocardiography. [11][12][13][14] Flow velocity at the left atrial appendage recorded by pulsed-Doppler using transesophageal echocardiography has emerged as a useful method. 15) Manning, et al 7) introduced LAEF, which is easily calculated from transthoracic echocardiography and can be compared among individuals over time.…”
Section: Discussionmentioning
confidence: 99%